(untitled) (Historia, 2021)
Confrontation and cooperation brings together the proceedings of the 1990 Krefeld Historical Symposia. American and German historians meet regularly in the city of Krefeld to discuss the historical dimensions of German-American relations. In 1990 these scholars discussed both the causes of German-American confrontation which culminated in American intervention against Germany in 1917, as well as the origins of close German-American cooperation in the 1920s.